Science Libraries Today: An Update on ARL Institutions - Chris Doty; Kristan Majors (Issues in Science and Technology Librarianship)
The goal of our study is to update the data on the state of science libraries at Association of Research Libraries (ARL) institutions and compare our data to previous studies. In 2023, 67% of the 120 ARL libraries had a science library. 152 science libraries remain open at ARL member institutions in Canada and the United States. Our findings show libraries are continuing to consolidate into multidisciplinary science libraries. Along with providing the highlights from our study, we also provide an updated dataset in Dataverse for other libraries to use in their own benchmarking studies.